Online Hospital Medical Dispute Resolution Model to Create Fairness - Seputra, Hawreyvian Rianda; Martien, Dhoni (Rechtsvinding, 2025)
This research aims to develop an online medical dispute resolution model in hospitals to create fairness for patients and medical personnel. The method used is a qualitative study with a descriptive analysis approach, collecting data through observation, interviews, and literature studies on the mechanism of medical dispute resolution and the application of digital technology in the process. The focus of the research is focused on how online systems can provide transparent, efficient, and easily accessible access for all relevant parties. The results of the study show that the use of an online medical dispute resolution model is able to increase the effectiveness and efficiency in handling dispute problems in hospitals. This technology-based process not only speeds up communication and decision-making, but also reduces administrative burdens and reduces the potential for prolonged conflicts. The model allows for neater and more transparent documentation, helping to maintain accountability and integrity of the settlement process. In addition, the implementation of the online system can increase patient and medical satisfaction because case resolution becomes faster and communication is more open, creating a greater sense of justice in health services.